A Guide for Implementing a Patent Strategy : How Inventors, Engineers, Scientists, Entrepreneurs, and Independent Innovators Can Protect Their Intellectual Property. - Rimai, Donald S. (John Wiley & Sons, Incorporated, 2018)
This book is aimed at the innovators who drive the advances from which we all benefit. This includes scientists, engineers, technicians, managers, and entrepreneurs who want to financially benefit from their innovations. The book describes how to build patent portfolios that will properly protect your technology and be of financial benefit. The tools that innovators need to have to generate patents are presented in detail.